OS07.7.A Rate and type of recurrence of lower-grade gliomas submitted to functional neurosurgical approach: the impact of the extent of resection. (5th September 2022) - Gay, L; Rossi, M; Conti Nibali, M; Sciortino, T; Bello, L
Abstract: Background: In the last decade, different published studies enlightened the extent-of-resection (EOR) as an independent factor for progression-free-survival (PFS) in patients with lower-grade gliomas (LGG). Aim of this study was to evaluate the impact of resections extending beyond FLAIR MRI abnormalities (supratotal), and eventual predictive factors and characteristics of recurrences. Material and Methods: We retrospectively analysed 460 patients submitted to surgery between 2007 and 2016 with a presumptive diagnosis of LGG, i.e., harbouring a mass lesion with no enhancement on contrast-administered T1-weighted MRI-sequences. All resections were performed according to functional boundaries determined by brain mapping/monitoring technique, without any patient or tumor a priori selection. The EOR was defined by analyzing pre- and post-operative volumetric FLAIR images. Results: The median pre-operative tumor volume was 43, 7 cm 3 . A supratotal resection (SPR) was achieved in 31.4%, a gross-total (GTR) in 41.1%, a subtotal (STR) in 27.5%. WHO grade II/III gliomas were diagnosed in 347 cases (319 IDH-mutant, 28 IDH-wildtype). Median follow-up was 60 months. SPR versus other EOR was associated to increased PFS (log rank test, p=.000) and malignant PFS (p=.000). Data were confirmed also after IDH status stratification. Rate of immediate and permanent post-op deficits among different EOR were comparable. Pre-op tumor volume, parietal and insular sites, eloquent location and dominant hemisphere tumors, and astrocytoma histology were associated to recurrence (p<.05). In 95.1% of cases recurrences were peri-cavitary. Lesions invading the corpus callosum presented minor rate of relapse; recurrences were most frequently diffuse and at distant sites. After SPR most common radiological appearance of recurrence was solid, while after GTR and STR percentages of solid and diffuse patterns were similar. Occurrence of distant recurrences, away from the resection cavity, were most associated to SPR. Conclusion: Our preliminary data suggests the dramatic impact in LGG of resections extending beyond FLAIR abnormalities on PFS and malignant PFS and on the characteristics of tumor recurrence.